Pengaruh Hard Skill dan Soft Skill Terhadap Kinerja Karyawan - Susamin, Jumiyati; Supriatna, Dadar (Mansion: Management and Business on Kebangsaan, 2025)
Introduction: In today’s global competition, companies increasingly recognize that employee performance depends not only on technical expertise but also on interpersonal and self-management abilities. This study investigates the role of hard skills and soft skills in shaping employee performance within the service industry. Background Problems: Despite the growing demand for high-performing employees, many organizations still struggle to balance technical competencies with non-technical capabilities. The central research question is: To what extent do hard skills and soft skills affect employee performance, both individually and simultaneously? Novelty: While previous studies have examined these variables in broader corporate settings, few have empirically tested their combined impact within a fast-growing food and beverage franchise context in Indonesia. This study provides context-specific evidence by focusing on Mixue Ice Cream & Tea employees in Bandung. Research Methods: This research employed a quantitative design with a sample of 30 employees selected through saturated sampling. Data were collected via questionnaires, observations, and interviews, and analyzed using multiple linear regression, including t-tests for partial effects and F-tests for simultaneous effects. Finding/Results: The results indicate that both hard skills and soft skills significantly and positively influence employee performance. Partial tests show that each variable contributes independently, while simultaneous analysis reveals a combined effect explaining 41% of performance variance. Conclusion: The study concludes that enhancing both technical expertise and interpersonal abilities is crucial to improving employee performance. Organizations should therefore prioritize integrated training and development programs that strengthen hard and soft skills to remain competitive in the service sector.